Applicability of prompt gamma-ray analysis to initial classification of meteorites - Naoki, Shirai; Mitsuru, Ebihara (2017)
第8回極域科学シンポジウム/個別セッション：[OA] 南極隕石 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OA] Antarctic meteorites Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object